SLACK RESOURCES, FAMILY OWNERSHIP AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Shoimah, Irma Lailatus; Aryani, Y Anni (Universitas Muhammadiyah Malang)
Our goal is to examine the impact of slack resources and family ownership on corporate social responsibility disclosure. Content analysis is used to measure the CSR disclosure based on the GRI-G4 index which consists of 91 items. This study also uses age, size, and leverage as control variables. A total of 139 samples of manufacturing companies registered on the Indonesia Stock Exchange in 2017 met the criteria using the purposive sampling method. The hypothesis was tested using multiple regression analysis techniques. We found that slack resources have a significant positive effect on CSR disclosure and family ownership has a significant negative effect on CSR disclosure. As control variables, size has a significant effect, while leverage and age have no effect on CSR disclosure.